Common and uncommon sources of growth in Asia Pacific - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
This paper embarks to analyse the role of exports and investment supposed to be major sources of economic growth in Asia Pacific. Therefore at first, the cointegration properties of exports, capital formation and GDP are examined in vector error correction models (VECMs). The results confirm the crucial role of exports and investment in the Asian growth dynamics. In a second stage, the structural shocks are identified by short- and long-run restrictions. These shocks, as well as the corresponding dynamic responses, are then correlated across all sample countries to provide insight into the depth of regional coherence. At last, the identified trends are explained by various macroeconomic variables.
Keywords: O11; F15; C32; 330; Economic Growth; Structural VECM; Export; Investment; Asia Pacific; Exportinduziertes Wachstum; Direktinvestition; Kointegration; Schock; Asiatisch-pazifischer Raum